Dietary convergence induces individual responses in faecal microbiome composition - Gwen Falony; Séverine Vermeire; Raul Y Tito; Sara Vieira-Silva; Jeroen Raes; Christophe Matthys; João Sabino; Sebastian Proost; Astrid Vermeulen; Erik Bootsma; Gunter Kathagen; Jorge F Vázquez-Castellanos (eGastroenterology)
Background Dietary variation has been identified as a key contributor to microbiome diversification. However, assessing its true impact in a cross-sectional setting is complicated by biological confounders and methodological hurdles. We aimed to estimate the impact of a reduction of dietary variation (dietary convergence) on faecal microbiota composition among individuals consuming a Western-type diet.Methods 18 healthy volunteers recruited in the region of Flanders (Belgium) were followed up for 21 days. Participants were allowed to consume their habitual diet during a baseline and follow-up period (7 and 8 days, respectively), intersected by a 6-day intervention during which dietary options were restricted to oat flakes, whole milk and still water. Faecal samples were collected on a daily basis. Quantitative microbiome profiles were constructed, combining 16S rRNA gene amplicon sequencing with flow cytometry cell counting. Blood samples were taken at the beginning and end of each study week.Results While the intervention did not affect transit time (as assessed through the analysis of stool moisture), consumption of the restricted diet resulted in an increased prevalence of the Bacteroides2 microbiome community type. Microbial load and Faecalibacterium abundance decreased markedly. Despite dietary restrictions, no convergence of microbial communities (reduction of interindividual and intraindividual variation) was observed. The effect size (ES) of the intervention on genus-level microbiome community differentiation was estimated as 3.4%, but substantial interindividual variation was observed (1.67%–16.42%).Conclusion The impact of dietary variation on microbiome composition in a Western population is significant but limited in ES, with notable individual exceptions. Dietary convergence does not invariably translate into interindividual convergence of faecal microbial communities.